ANTI-DIABETES ACTIVITY AND PHYTOCHEMICAL ANALYSIS OF DURIAN FRUIT FRUIT METHANOL FRACTION - Rabbaniyyah, Muthi'ah; Suciati, Anugerah (International Islamic Medicine Forum, 2023)
Durian fruit peel is one of the natural ingredients that are considered environmental waste by the people of Indonesia. The use of durian skin is starting to be sought, especially in the treatment of degenerative diseases, one of which is diabetes. Testing of activity as antidiabetic on durian fruit peel needs to be done. Durian fruit peel fraction was made by liquid-liquid partition which was then carried out to make compounds and in vitro antidiabetic potency test. Identification of compounds in the methanol fraction by qualitative TLC and UV-Vis spectrophotometry quantitatively showed high levels of rutin flavonoids. The flavonoid-rich fraction of rutin from durian peel was found to be effective in inhibiting alpha-glucosidase. The methanol fraction of durian fruit peel inhibited the activity of the alpha-glucosidase enzyme significantly (IC50 of 24) and did not differ much from conventional drugs, namely acarbose (IC50 of 23). This study showed that the methanol fraction of durian fruit peel which contains high routine flavonoid compounds has an active ability in in vitro antidiabetic testing.